Causes for procrastination in a unique educational workplace. Issue 3 (3rd July 2018) - Hen, Meirav
Abstract: Teachers in hospitals are a unique phenomenon. Their students are sick, hospitalized children with a range of physical, emotional, and cognitive needs. Teachers are expected to be dynamic, flexible, creative, open-minded, and efficient to function in the most appropriate manner. However, a recent study showed that these teachers tend to procrastinate on some of the most common tasks that teachers perform on a daily basis in the regular school system. The present study was an initial investigation into the reasons for procrastination in teachers who work in two hospitals in Israel. Thirty-two teachers were interviewed. The findings indicated that the primary reason for procrastination among teachers in the hospital was professional role ambiguity, with emotional factors and situational determinants which were identified. Future research should further explore reasons for procrastination in the workplace, in general, and its association with professional role ambiguity specifically.